Revolutionizing The Halal Food Industry: The Crucial Role of Green Halal Supply Chain in Pakistani Companies - A Compelling Theoretical Framework - Safiullah Junejo; M. Luthfi Hamidi; Saba Anwar (Journal of Islamic Economic Laws, 2023)
The 13th Five Year Plan 2016-2020 (FYP) says that Pakistan wants to be a global hub for Halal food, and the country is on track to reach this goal by 2025. However, the progress needs to be supported by a complete ecosystem that lets the Halal supply chain close the compliance loop. So, calling for sustainable development to help strengthen the definition of "Halal." Even though they want to, the Halal food industry is not ready to use green practices yet, and the issues are still new and changing. The food industry is one of the leading causes of environmental problems, creating a lot of waste. Promoting sustainability in the production of Halal food can help them to reduce their impact on the environment. This will help Pakistan because other countries will recognize Pakistani Halal standards not only as a sign of cleanliness and safe but also as a sign of eco-friendly practices. So, the green Halal supply chain is now crucial to making the world a Halal hub. In response to these needs, the goals of this study are: first, to find out what green practices are used to manage the Halal food supply chain in collaboration with the supplier and customer; second, to find out what sustainable performance results from using green practices; and third, to find out if supplier-customer collaboration lessens the effect of green practice on sustainable performance. The goals of this study will be met through a mix of quantitative and qualitative methods. Overall, this study is supposed to develop a model that gives a complete picture of the Green Halal supply chain regarding how suppliers and customers work together to do green practices. The model can help the business world and policymakers figure out what green practices they can work together on and the pros and cons of doing so. Pakistan can build its reputation as the world's top Halal hub by joining the Green Halal supply chain.